ANALYSIS OF STUDENTS' ERRORS IN SOLVING WORD PROBLEMS ABOUT SOLID FIGURES IN FIFTH GRADE OF SDN TAMBAKREJO, PURWOREJO REGENCY, IN ACADEMIC YEAR OF 2020/2021. - Zahrotun Nafi; Tri Saptuti Susiani; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The study aimed: (1) to analyze the types of students’ errors of fifth grade in solving math word problems about solid figures, (2) to describe the factors causing students' errors in solving math word problems about solid figures, (3) to describe solutions to overcome students’ errors in solving math word problems about solid figures in fifth grade of SD Negeri Tambakrejo. The research was a qualitative case study method. The subjects were 24 fifth grade students. Data collection techniques included observation, tests, interviews, and documents. Data analysis techniques were data reduction, data presentation, and verification. The results showed that: (1) the types and the percentage of students’ errors were: reading error = 5.3%, comprehension error = 20.7%, transformation error= 24%, process skill error= 11%, encoding error= 20.5%. (2) The factors causing students’ errors were internal factors and external factors. (3) The solutions to solve students’ errors were (a) the students were discipline to do word problems step-by-step, (b) the teachers emphasized the students in order to write steps in solving word problems completely, (c) the teachers emphasized the students about the basic concept in doing word problems, (d) the teachers applied effective and creative learning models.